Transverse relaxation rates of pulmonary dissolved‐phase Hyperpolarized 129Xe as a biomarker of lung injury in idiopathic pulmonary fibrosis - Kammerman, Jeff; Hahn, Andrew D.; Cadman, Robert V.; Malkus, Annelise; Mummy, David; Fain, Sean B. (Magnetic resonance in medicine, 2020)
Purpose The MR properties (chemical shifts and R2∗ decay rates) of dissolved‐phase hyperpolarized (HP) 129Xe are confounded by the large magnetic field inhomogeneity present in the lung. This work improves measurements of these properties using a model‐based image reconstruction to characterize the R2∗ decay rates of dissolved‐phase HP 129Xe in healthy subjects and patients with idiopathic pulmonary fibrosis (IPF). Methods Whole‐lung MRS and 3D radial MRI with four gradient echoes were performed after inhalation of HP 129Xe in healthy subjects and patients with IPF. A model‐based image reconstruction formulated as a regularized optimization problem was solved iteratively to measure regional signal intensity in the gas, barrier, and red blood cell (RBC) compartments, while simultaneously measuring their chemical shifts and R2∗ decay rates. Results The estimation of spectral properties reduced artifacts in images of HP 129Xe in the gas, barrier, and RBC compartments and improved image SNR by over 20%. R2∗ decay rates of the RBC and barrier compartments were lower in patients with IPF compared to healthy subjects (P < 0.001 and P = 0.005, respectively) and correlated to DLCO (R = 0.71 and 0.64, respectively). Chemical shift of the RBC component measured with whole‐lung spectroscopy was significantly different between IPF and normal subjects (P = 0.022). Conclusion Estimates for R2∗ in both barrier and RBC dissolved‐phase HP 129Xe compartments using a regional signal model improved image quality for dissolved‐phase images and provided additional biomarkers of lung injury in IPF.